LAS EMOCIONES DE JÓVENES UNIVERSITARIOS CON RESPECTO AL SEXO, RENDIMIENTO ESCOLAR Y TRAYECTORIA ESCOLAR. UN ESTUDIO COMPARATIVO - Norma Angélica Ortega Andrade; Rubén García Cruz; Ana María Rivera Guerrero; David Jiménez Rodríguez (European Scientific Journal, ESJ, 2014)
Emotional skills are fundamental to human life. The model of Mayerand Salovey (1990) considers four basic skills of emotional intelligence (EI):perceive, understand, express and regulate. EI influences the social,educational and personal development of college students (Extremera &Fernández-Berroca , 2004). There are many studies that show the differencesbetween men and women, some studies in education, reported conflictingresults in the relationship: IE and school performance (RE), few studies haveconsidered the transition from one school level to examine the context therelationship between EI and RE. This study aims to identify the emotionalskills of university students with respect to gender, level of educationalachievement and school career. Type descriptive-comparative, quantitativestudy of transactional design.Involved 300 college students(144 men and 156women) from the Institute of Health Sciences at the Autonomous Universityof the State of Hidalgo. The analysis was performed with the test Chi Squarestatistic (X²). Absence of statistically significant differences between the REand level of school career (NTE) and the three emotional skills variableswere identified, therefore, analyzed individually each skill by emotion (love,sadness, happiness, anger and fear) with for each classification variable (RE,NTE and sex), showing statistically significant in each of these differences.